PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PT. BANK CENTRAL ASIA TBK. KCP TEBET TIMUR - Imhar, Imhar; Kurnaesih (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2022)
The implementation of this research aims to analyze and see how the handling of complaints of PT BANK CENTRAL ASIA TBK KCP Tebet Timur against customer satisfaction. The nature of the implementation of this research is in the form of qualitative research, in addition to the use of its own type of research is to deepen the research subject in the form of employee service both teller and customer service and also an overview of Bank Central Asia customer satisfaction. The sample number is calculated based on the average number of customers of PT Bank BCA Tbk Kcp Tebet Timur and the number of tellers and the number of customer service divided by the number of working days during the month. The data was obtained from questionnaire answers that have been shared with customers and employees of PT BANK CENTRAL ASIA TBK KCP Tebet Timur as respondents in this study. The results of the study were presented in the form of descriptive to describe the results of observations made from the data obtained and then came to the conclusion that the handling of complaints made by customer service to customers of PT Bank Central Asia Tbk had a significant influence on customer satisfaction after they expressed their complaints so that 14.9% results were obtained as customer satisfaction in which there is an Emphaty dimension and 12.18% of the Responsiveness dimension to the attitude given by BCA Kcp Tebet Timur employees . Therefore, the attitude of employees of PT Bank Central Asia Tbk is also an indicator in responding to customer complaints. Employees who have a positive attitude in handling complaints will make customers feel more comfortable.